Can the tolerance of aerial exposure of the green-lipped mussel Perna viridis (L.) as a potential biomonitoring tool to assess Cd and Cu contamination? A laboratory study - Yap, Chee Kong; Ismail, Ahmad; Tan, Soon Guan (Scientific Publishers, 2009)
The nature of the intertidal area that is constantly affected by the daily tidal changes is an interesting subject for scientific studies. We investigated the potential of tolerance of survival in the air as a tool to assess Cd and Cu contamination under laboratory conditions. The experimental methodology was designed to provide evidence that metal-stressed mussels had reduced tolerance to survive in the air when compared to control mussels. The lower condition index (CI) values and higher CI reduction with significantly (P< 0.05) higher metal levels in the stressed mussels than unstressed (control) mussels indicated that much of the stored reserves were channeled to synthesize metallothionein and to other homeostatic mechanisms during changes of the metabolic pathways. The present finding suggest the use of tolerance to aerial exposure as a potential biomonitoring tool (a physiological response) to Cci and Cu contamination since it was measured at the level of the whole mussel, rapid, easily quantified and relatively inexpensive.